ANALISIS JALUR EVAKUASI PADA GEDUNG FAKULTAS TEKNIK UNIVERSITAS PATTIMURA DENGAN METODE ALGORITMA DIJKSTRA - Umahuk, M Ishan; Buyang, Christy Gery; Oppier, Imran (Universitas Pendidikan Indonesia (UPI), 2025)
The Faculty of Engineering building is one of the science faculties at Pattimura University which consists of three floors. There is currently no evacuation route in the Engineering Faculty building that shows an exit or path to a safe place. This building experienced an earthquake so this caused panic among the building's occupants when they wanted to save themselves. Therefore, the Faculty of Engineering building needs to plan evacuation routes and gathering points to anticipate if a disaster occurs. Evacuation routes are very important in multi-storey buildings, especially during disasters such as earthquakes and fires. Having an evacuation route can prevent building occupants from scattering but can position them to go through and see the information on the evacuation display to get to the assembly point quickly and reduce the number of victims caused by panic when a disaster occurs.The aim of this research is to find out the shortest distance from the evacuation route for each floor to the gathering point and to find out the shortest distance from the temporary gathering point to the final gathering point using the Dijkstra algorithm. The research method used in this research is the Dijkstra algorithm method. From the results of research that has been carried out using distance calculations and measurements as well as marking evacuation route displays, the shortest distance on the first floor is obtained: 12.5 m, the shortest distance on the second floor: 35.4 m, the shortest distance on the third floor: 46.5 m, to get to the gathering point (assembly point